Subject–Motion Correction in HARDI Acquisitions: Choices and Consequences - Elhabian, Shireen; Gur, Yaniv; Vachet, Clement; Piven, Joseph; Styner, Martin; Leppert, Ilana R.; Pike, G. Bruce; Gerig, Guido (Frontiers in Neurology, 2014)
Diffusion-weighted imaging (DWI) is known to be prone to motion artifacts originating from subject movement, cardiac pulsation and breathing. Given the necessity for rigorous quality control and motion correction, users are often left to use simple heuristics to select correction schemes, which involve simple qualitative viewing of the set of DWI data, or the selection of transformation parameter thresholds for detection of motion outliers. Whereas post-acquisition motion correction is widely performed, the effects and consequences of the selection of motion correction schemes on the final analysis, and the eventual risk to introduce confounding factors when comparing populations, are much less known and far beyond simple intuitive guessing. Hence, standard users lack clear guidelines and recommendations in practical settings. This paper reports a comprehensive evaluation framework to systematically assess the outcome of different motion correction choices commonly used by the scientific community on different DWI-derived measures. We make use of human brain HARDI data from a well controlled motion experiment to simulate various degrees of motion corruption and noise contamination. Choices for correction include exclusion/scrubbing or registration of motion corrupted directions with different choices of interpolation, as well as the option of interpolation of all directions. The comparative evaluation is based on studying the impact of motion correction using four different metrics which quantify (1) similarity of fiber orientation distribution functions, (2) deviation of local fiber orientations, (3) global brain connectivity, and (4) the reproducibility of prominent and anatomically defined fiber tracts. Effects of various motion correction choices are systematically explored and illustrated, leading to a general conclusion of discouraging users from setting ad-hoc thresholds on the estimated motion parameters beyond which volumes are claimed to be corrupted.